Administração de medicamentos endovenosos: avaliação do programa de treinamento para promoção da segurança do paciente pediátrico com cardiopatia hospitalizado - Custódio, Ires Lopes (2019)
This study aimed to evaluate the training program for the nursing team on the intravenous drug (IV) administration process effectiveness to promote the hospitalized pediatric patients heart disease safety. Evaluative, quasi-experimental study, time series, carried out in pediatric cardiac units of a public hospital from Fortaleza-Ceará, through three phases: Phase 1 - Pre-training: socio-demographic and professional profile Characterization of the 38 training program participants and their evaluation; Phase 2 - Training: training implementation on the Nursing team according to Kirkpatrick and Kirkpatrick (2010) 10 steps; Phase 3 - Post-training: four assessment levels Evaluation: Reaction (Level 1) questionnaire applied after training; Learning (Level 2) a questionnaire was applied immediately and six months after training (post-test); Selfreported and observed behavior (Level 3), which the self-reported behavior assessment was made by applying a questionnaire immediately and six months after training and observed behavior evaluation by using a checklist six months after training; and Results (Level 4) by reporting incidents with EV medications from pediatric units during six months after training. Study approved by the Ethics and Research Committee (CAE 68896217.0.3001.5039). Data were processed in SPSS 20.0 and organized in tables with absolute and relative frequencies, quantitative variables averages and standard deviations. For before and after proportions comparison McNemar test was used. Among the periods Friedman test (whether three or more periods) and Wixocon test (if only two) were used. The training proportions about reported incidents comparison was performed using a binomial test for paired proportions. Analyzes with p <0.05 were considered statistically significant. As results of participants characterization, were achieved: female gender (100%), age group average 41,26±11,8; nurses (52.6%) and nursing technician (47.4%); professional experience with pediatric patients varied from 3 to 33 years, with 9.84 ± 6.8 average. In the participants reaction evaluation, ten items, in a group of 12, were satisfactory (p <0.0001). In the assessment of learning, there was an increase in the number of correct answers to the questions related to learning before and after training, with progressive evolution, considering that right answers presented achievements rate higher than 80%. In the self-reported behavior by the Nursing team evaluation, there was an increase in commitment and willingness to improve assistencial practice (p = 0.012) and sensitivity to work properly in medication administration (p = 0.039); In the observed behavior, the professionals' performance improved in 18 of all 39 actions from the IV medication administration process after training, with significant difference (p <0.05). In the outcome assessment, incidents with intravenous medication were reduced after training, from 11.7%, in 2018, to 9.7%, in 2019. Therefore, the intravenous medication administration process in hospitalized pediatric patients with heart disease training program presented positive effects on nursing professionals' reaction, learning and behavior in assistencial practice leading to positive results in incident prevention and patient safety promotion during the drugs administration in cardiac pediatrics.